Comparative Analysis of UFMC and GFDM Modulation Techniques in 5G New Radio - Divya Jain, Debendra Kumar Panda, Smita Prajapati, Suyog Munshi, Mahima Jain, Supriya Kalamkar (Journal of Neonatal Surgery, 2025)
In the evolving landscape of Fifth Generation (5G) New Radio (NR), waveform design plays a crucial role in meeting the diverse requirements of enhanced mobile broadband (eMBB), ultra-reliable low-latency communication (URLLC), and massive machine-type communication (mMTC). Among the contenders proposed as alternatives to conventional Orthogonal Frequency Division Multiplexing (OFDM), Universal Filtered Multi-Carrier (UFMC) and Generalized Frequency Division Multiplexing (GFDM) have gained significant attention in 5G due to their superior spectral containment and flexibility. This paper presents a comparative analysis of UFMC and GFDM modulation techniques with a focus on Bit Error Rate (BER) and Power Spectral Density (PSD) performance. The BER performance of both waveforms is evaluated across varying signal-to-noise ratio (SNR) levels. Additionally, the spectral characteristics of UFMC and GFDM are analysed to quantify their out-of-band (OOB) emissions. Results demonstrate that while UFMC offers improved spectral localization with significantly lower OOB leakage, GFDM achieves better BER performance in moderate to high SNR regimes due to its flexibility in pulse shaping and time-frequency localization. The results provide insights that can be used for waveform selection in 6G networks, where UFMC’s spectral efficiency supports high-frequency bands, while GFDM’s flexibility and low-latency traits align with ultra-reliable, real-time applications.